2011
DOI: 10.1007/s11663-011-9518-1
|View full text |Cite
|
Sign up to set email alerts
|

Grain Floatation During Equiaxed Solidification of an Al-Cu Alloy in a Side-Cooled Cavity: Part I—Experimental Studies

Abstract: Experimental studies were performed to investigate the role and influence of grain movement on macrosegregation and microstructure evolution during equiaxed solidification. Casting experiments were performed with a grain-refined Al-Cu alloy in a rectangular sand mold. For the aluminum alloy studied, the equiaxed grains are lighter than the bulk melt and thus float up. Experiments were designed to investigate floatation phenomena of equiaxed grains in the presence of thermosolutal convection. Cooling curves wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Wu's simulation study did not take account of the movement of equiaxed grains, which can markedly influence the solidification structure of castings. 22,23) Also, the solidification structure refinement of Al-Cu alloys in super-gravity field has been investigated systematically in our recent study, 24) which demonstrated that the "crystal rain" caused by super-gravity contributed to the grain refinement.…”
Section: Effect Of Super-gravity Field On Grain Refinement and Tensilmentioning
confidence: 96%
“…Wu's simulation study did not take account of the movement of equiaxed grains, which can markedly influence the solidification structure of castings. 22,23) Also, the solidification structure refinement of Al-Cu alloys in super-gravity field has been investigated systematically in our recent study, 24) which demonstrated that the "crystal rain" caused by super-gravity contributed to the grain refinement.…”
Section: Effect Of Super-gravity Field On Grain Refinement and Tensilmentioning
confidence: 96%
“…IN a companion paper, Kumar et al [1] reported a controlled set of experiments to study the influence of the floatation of solid crystals on macrosegregation and microstructure formation during equiaxed solidification.…”
Section: Introductionmentioning
confidence: 99%
“…[3,5,26] Yang et al [3] and Chang and Stefanescu [26] proposed a simplified treatment by using a singledomain framework for movement of equiaxed grains in which the solid grains and the liquid move with the same velocity, and an effective viscosity is used. Their model assumes zero relative velocity between the solid and the liquid phases, which is not the case for larger floating equiaxed grains as has been shown in Kumar et al [1] A splitting scheme for coupling macroscopic transport and grain growth during solidification within a framework of a multicomponent, two-phase solidification model was presented by Combeau and coworkers. [27][28][29] A key feature in the proposed solution scheme is that the contribution to the solid mass and solute balance caused by transport and grain growth are solved in two stages by applying an operator splitting algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations